2008
DOI: 10.1074/jbc.m708994200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Mechanism of pH-dependent Ligand Binding and Release by the Cation-dependent Mannose 6-Phosphate Receptor

Abstract: The cation-dependent mannose 6-phosphate receptor (CD-MPR) is a key component of the lysosomal enzyme targeting system that binds newly synthesized mannose 6-phosphate (Man-6-P)-containing acid hydrolases and transports them to endosomal compartments. The interaction between the MPRs and its ligands is pH-dependent; the homodimeric CD-MPR binds lysosomal enzymes optimally in the pH environment of the trans Golgi network (pH ϳ 6.5) and releases its cargo in acidic endosomal compartments ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 36 publications
(38 reference statements)
5
49
0
Order By: Relevance
“…Alternatively clustering of cargo receptors by COPII coat subunits at ER exit sites could increase receptor affinities for cargo and then reverse ligand binding upon vesicle uncoating. In these models, the oligomeric arrangement of Erv26p and other known cargo receptors could provide a means for inducing conformational changes that favor cargo binding in the ER and then shift to an unbound closed state in post-ER compartments as observed for other types of multimeric receptor proteins (47,48). In the case of Erv26p, our studies show that deletion of the C-terminal tail sequence uncoupled coat recognition from cargo binding suggesting that COPII clustering of cargo receptors does not regulate cargo interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively clustering of cargo receptors by COPII coat subunits at ER exit sites could increase receptor affinities for cargo and then reverse ligand binding upon vesicle uncoating. In these models, the oligomeric arrangement of Erv26p and other known cargo receptors could provide a means for inducing conformational changes that favor cargo binding in the ER and then shift to an unbound closed state in post-ER compartments as observed for other types of multimeric receptor proteins (47,48). In the case of Erv26p, our studies show that deletion of the C-terminal tail sequence uncoupled coat recognition from cargo binding suggesting that COPII clustering of cargo receptors does not regulate cargo interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although structure-based protein design is a promising technique for improving molecular function (12)(13)(14)(15), it is yet difficult to specifically modulate pH sensitivity of a protein-protein interaction without an associated loss of inherent function and/or structural stability. Some naturally occurring proteins undergo substantial conformational change by pH shift, thereby achieving pH-dependent binding for small molecules (2,4,16,17). However, artificial design of an equivalent mechanism involving conformational change is highly problematic.…”
mentioning
confidence: 99%
“…Olson et al have shown that conformational changes happen in the MR CRDs at pHs over 7.5, and they predicted no binding would occur at that pH, however, they did not perform SPR studies [298]. This correlates with previous results where the use of a high pH regeneration buffer (10 mM, NaOH, pH 9.5) was shown to change the baseline dramatically.…”
Section: )supporting
confidence: 78%